Design Thinking in Higher Education Case Studies: Disciplinary Contrasts between Cultural Heritage and Language and Technology - Griffith-Bourn, Mary Margaret; Lechuga-Jiménez, Clotilde (MDPI, 2024)
Design thinking is a set of cognitive, strategic, and practical procedures used in innovation. This article argues that this approach varies across disciplines. The contexts for this study are two higher educational frameworks where language and technology have different aims and target unique skill sets and where transdisciplinarity is crucial. In our contrastive case study, we use a four-step model to compare two contexts. QUAN(qual) → QUAL mixed methodology is used which includes a quantitative and a qualitative comparative analysis. Context one takes place in an education faculty and focuses on developing cultural heritage. Context two takes place within a research project on linguistics and telecommunications involving linguistic analysis and bioelectrical measurement. Our findings indicate that there are clear and specific differences between the two domains when approaching design thinking. We observe that engineers seem to have a tangible final product in mind at each step of the process, while in the social sciences, the construct is more humanistic in its approach and works towards multiple tangible goals, including an examination of the existing needs in the community. The novelty of the study is the applied approach it takes in treating transdisciplinarity as a skill that is essential both in research as well as in the teaching–learning process.
Keywords: Educación superior; Higher education; Transdisciplinarity; Design thinking; Language and machine learning; Cultural heritage